Understanding the Overlap of Online Offending and Victimization: Using Cluster Analysis to Examine Group Differences - Parti, Katalin (Victims & offenders, 2022)
Criminal offending and victimization often overlap in both the virtual and offline worlds. However, scholars are still unsure how the offending-victimization relationship plays out between the online and offline worlds. Using a sample of 2,491 adults, four clusters are discovered: 1) those unlikely to have offended or been victimized, 2) those who had online victimization and offending experiences, 3) Those who have been victimized offline and online, but who are unlikely to have offended, and 4) individuals who were victims both online and offline and offended online. Thus, the offending-victimization overlap may be common, but it is certainly not exclusive.